The effect of sustainability certification for export on operational profitability of Malaysian palm oil companies - Shahida Shahimi,; Hafizuddin-Syah B.A.M,; Siti Hanisah Fuad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Malaysia is the world’s second largest palm oil producer with 17.4 million tonnes palm oil produced in 2016. The production is for both domestic and export which contribute towards country’s income and economic growth. Despite the significant contribution to the economy, being one of the plantation sectors, Malaysian palm oil has been criticized by the western communities for causing environmental problems such as deforestation and open burning. Hence, it is important for the palm oil companies to ensure sustainable operation and production. The introduction of certified sustainable palm oil (CSPO) or sustainability certification, for instance, Roundtable on Sustainable Palm Oil (RSPO) and Malaysian Sustainable Palm Oil (MSPO), encourages the sustainable practices by the industry players. Recently, the government had announced the mandatory MSPO-certification in Malaysia by end of 2019. At present, there are only 43.6% Malaysian palm oil companies with at least one certification. The mandatory certification had raised concern among companies on additional costs of adoption which eventually will affect profitability. Moreover, sustainability certifications will only benefit the exporting companies for international market penetration. The question is how important does this certification to the exporting companies as compared to others? This study will analyse the effect of sustainability certification on operational profitability of Malaysian palm oil exporting companies. This study employs generalised least square (GLS) estimation on 17 listed palm oil companies in Bursa Malaysia from 2009 to 2015. The result shows that there is no significant difference in operating profitability due to sustainability certification between the palm oil exporting than the non-exporting companies. The findings indicate that sustainablity practice through RSPO or/and MSPO motivates Malaysian palm oil companies to produce certified palm oil for international and domestic markets, which in line with sustainable development goal (SDG) no. 12 (Ensure Sustainable Consumption and Production Patterns) by the United Nations (UN).